2022
DOI: 10.1038/s41556-022-01021-8
|View full text |Cite
|
Sign up to set email alerts
|

Gradual differentiation uncoupled from cell cycle exit generates heterogeneity in the epidermal stem cell layer

Abstract: Highly regenerative tissues continuously produce terminally differentiated cells to replace those that are lost. How they orchestrate the complex transition from undifferentiated stem cells towards post-mitotic, molecularly distinct and often spatially segregated differentiated populations is not well understood. In the adult skin epidermis, the stem cell compartment contains molecularly heterogeneous subpopulations1–4 whose relationship to the complete trajectory of differentiation remains unknown. Here we sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 57 publications
(99 reference statements)
1
29
0
Order By: Relevance
“…Although these observations await confirmation by monitoring DeltaA protein -we currently lack an antibody detecting DeltaA in adult zebrafish NSCs-, they suggest that sister deltaA pos cells are generally not equivalent, and that fate acquisition is a progressive process along the division sequence of each deltaA pos NSC. This is highly reminiscent of the progressive transition from commitment to differentiation described in mouse skin stem cells 53 . There was a trend but no clear-cut AA-related rule associated with the assignment of deltaA :GFP differences between daughters (Figure S4D).…”
Section: Discussionmentioning
confidence: 83%
“…Although these observations await confirmation by monitoring DeltaA protein -we currently lack an antibody detecting DeltaA in adult zebrafish NSCs-, they suggest that sister deltaA pos cells are generally not equivalent, and that fate acquisition is a progressive process along the division sequence of each deltaA pos NSC. This is highly reminiscent of the progressive transition from commitment to differentiation described in mouse skin stem cells 53 . There was a trend but no clear-cut AA-related rule associated with the assignment of deltaA :GFP differences between daughters (Figure S4D).…”
Section: Discussionmentioning
confidence: 83%
“…The epidermis is a highly regenerative organ involving the continual differentiation of cells from the basal stem cell layer to form the functional barrier of our skin. Cells within the stem cell layer will continually alter their transcriptome, delaminate from the stem cell compartment, and move apically/outward to form the overlaying differentiated layer (called spinous) over the course of 3–4 days ( Cockburn et al, 2022 ; Mesa et al, 2018 ; Figure 2A ). Previous studies have demonstrated that basal stem cells and differentiated spinous cells have different nuclear volumes and numbers of pericentromeric clusters ( Gdula et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…We next wondered whether the transition in chromatin compaction occurs slightly later during differentiation in cells actively delaminating, located in between the basal and spinous layer ( Cockburn et al, 2022 ; Figure 3—figure supplement 1B ). Strikingly, we noticed the chromatin of these cells spin over the course of the timelapse ( Figure 3B , Video 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of type II keratins is confirmed by the fact that keratin 5 is often present in the basal layer of pseudostratified epithelium, while keratin-14 expression is sparse [ 43 , 50 , 52 , 59 , 64 ]. However, recently published details about mouse epidermal keratinocytes differentiation revealed the expression of keratin 10 belonging to type I of keratins prior to type II keratin 1 at a protein level [ 181 ]. These novel results indicate the importance of further investigation of the transcription activation of paired keratins within the keratin loci for the identification of the basic principles of their coordinated expression.…”
Section: Keratin Expression Patternmentioning
confidence: 99%